2021
DOI: 10.1080/02697459.2021.1905991
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Covid-19 Pandemic: Canvassing Opinion from Planning Professionals

Abstract: By the end of 2020, the COVID-19 pandemic had exceeded 83 million cases worldwide. Given the shared origins of planning and public health, new living and social conditions have prompted an interest in how urban planning could respond to the pandemic's associated implications. In 2020, a national online survey Plan My Australia was conducted among planning experts (n = 161), in part, to identify new challenges facing urban planning and design due to the pandemic. The findings reported here revealed that many ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The recovery from lockdowns will not be immediate ( Pratt, 2020 ) and will require changes to how we think about policy and science ( Hardin, 2021 ; Kob, 2020 ). We will see many adjustments to how we live our lives and plan our spaces ( Bolleter et al, 2021 ). As we move to a post COVID-19 world our results may have implications for performers, for donors and for (local) governments as street performers return to the street.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery from lockdowns will not be immediate ( Pratt, 2020 ) and will require changes to how we think about policy and science ( Hardin, 2021 ; Kob, 2020 ). We will see many adjustments to how we live our lives and plan our spaces ( Bolleter et al, 2021 ). As we move to a post COVID-19 world our results may have implications for performers, for donors and for (local) governments as street performers return to the street.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the studies conducted during the pandemic period revealed that the epidemic required a reconsideration of the city in terms of size, urban density, self-sufficiency, use of public transport, providing open space, housing design and better planning for the future (Bolleter, et al, 2021).…”
Section: Sonuçmentioning
confidence: 99%
“…Several studies have been conducted in various countries and organizations investigating resident satisfaction and preferences during the pandemic [4][5][6].…”
Section: Introductionmentioning
confidence: 99%